Bubble-Free Propulsion of Ultrasmall Tubular Nanojets Powered by Biocatalytic Reactions - Ma, Xing (J Am Chem Soc, 2016)
[Image: see text] The motion of self-propelled tubular micro- and nanojets has so far been achieved by bubble propulsion, e.g., O(2) bubbles formed by catalytic decomposition of H(2)O(2), which renders future biomedical applications inviable. An alternative self-propulsion mechanism for tubular engines on the nanometer scale is still missing. Here, we report the fabrication and characterization of bubble-free propelled tubular nanojets (as small as 220 nm diameter), powered by an enzyme-triggered biocatalytic reaction using urea as fuel. We studied the translational and rotational dynamics of the nanojets as functions of the length and location of the enzymes. Introducing tracer nanoparticles into the system, we demonstrated the presence of an internal flow that extends into the external fluid via the cavity opening, leading to the self-propulsion. One-dimensional nanosize, longitudinal self-propulsion, and biocompatibility make the tubular nanojets promising for future biomedical applications.